AGRIBISNIS PERKEBUNAN DAN PERHUTANAN DALAM KERANGKA PARADIGMA BARU PENGELOLAAN SUMBERDAYA ALAM1 - , S. Sabarnurdin; , , P. Purwadi ([Yogyakarta] : Fakultas Kehutanan UGM, 2003)
In Indonesia, for the sake of avoiding sectoral confusion whether it belongs to agricultural or forestry domain, the word plantation has been translated differently into Perkebunan and Butan Tanaman (perhutanan). Both of them are similar in that being export-oriented characteristic except the type of trees they are planting. Again both of them facing similar problems which is rooted from the failure of their participation in the program of welfare improvement of local people. The new paradigm of natural resource management requires the changing of the existing management approach toward a &quot